FAKTOR YANG MEMPENGARUHI KEPUASAN MAHASISWA TERHADAP KUALITAS LAYANAN PERPUSTAKAAN - Mursid Dwi Hastomo Dwi Hastomo (Riset Manajemen dan Akuntansi, 2019)
This research aims to investigate the factors that influence the level of student satisfaction with campus library services in the Informatics Management study program and the most dominant factor in influencing student satisfaction with campus library services in the informatics Management study program. This research uses a quantitative approach, with a type of exploratory research. For this research population, all students are Informatics Management study programs, while the sampling method is random sampling. The results of this research are: the factor of service quality of library employees in the Informatic Management study program is good, the facility factor in the library of the Information Management study program is good, but there is a need to label information on a more detailed bookshelf. The most dominant factor in influencing student satisfaction with the quality of library services in the Informatics Management study program is the library employee services.